The impact of provider restrictions on abortion-related outcomes: a synthesis of legal and health evidence - Fiona de Londras; Amanda Cleeve; Maria I. Rodriguez; Alana Farrell; Magdalena Furgalska; Antonella F. Lavelanet (BMC, 2022)
Plain language summary This review identifies evidence of the impacts of provider restrictions on people seeking to access abortion and on abortion providers. It pursues a methodology designed to ensure the full integration of public health and human rights standards developed by the research team and published elsewhere. The evidence from this review points clearly to provider restrictions having negative implications for health outcomes, health systems, and human rights. This is especially important as international guidance provided by the WHO indicates best practice in provision and management of abortion and shows clearly that undue provider restrictions are not justified by reference to the nature and complexity of abortion.